Advancing Larger Democracy in Indonesia through Islamic Print Media - Akh. Muzakki (Al-Jami'ah: Journal of Islamic Studies, 2011)
Over the past one decade, Indonesia has been renowned for its achievement in consolidating and establishing democracy after having experienced thirty two year political authoritarianism. The power is now step by step leased back to the people. In the least form, people are little by little getting access to the processes of policy-making. Their aspirations, instead of being undermined, are considered to be as gradually important as those of political elites. This paper is an attempt to examine the role of print media in enhancing the democratisation processes through the analysis of the production of Islamic ideas within print media publication. For the purpose of simplification, print media publication can be regarded as part of the essential translation of the press, a pillar of democracy. As a focus of analysis, this paper deals with print publications, in the form of both Islamic books and magazines, produced by Muslim scholars or activists in Indonesia. Islamic books are presented by those produced by publishers, such as Mizan, Gema Insani Press, and Wihdah Press. Islamic magazines are presented by Sabili, Hidayah, and Jihadmagz.[Lebih dari satu dekade terakhir, Indonesia dikenal sebagai negara yang berhasil melakukan konsolidasi demokrasi setelah mengalami tiga puluh dua tahun otoritarianisme Orde Baru. Kekuatan politik secara perlahan dikembalikan ke rakyat. Setidaknya, rakyat sedikit demi sedikit semakin memiliki akses atas pembuatan kebijakan. Aspirasi mereka kemudian diperhitungkan dan dianggap penting seperti aspirasi elit politik. Artikel ini mendiskusikan peran media-cetak dalam proses demokratisasi, yaitu dengan mengalisis produksi gagasan-gagasan tentang Islam yang dimuat dalam media cetak. Secara umum, media cetak merupakan salah satu bentuk pers yang menjadi salah satu pilar demokrasi. Pembahasan dalam artikel ini difokuskan pada buku dan majalah yang diterbitkan oleh ulama atau aktifis di Indonesia. Mizan, Gema Insani Press, dan Wihdah mewakili penerbit buku, sementara Sabili, Hidayah dan Jihadmagz mewakili kelompok majalah.]